Genetic Effects of Chromosomes 1, 4, and 18 from Three Tetraploid Gossypium Species in Topcrosses with Five Elite Cultivars. Issue 3 (16th June 2017) - Jenkins, Johnie N.; McCarty, Jack C.; Campbell, B. Todd; Hayes, R. W.; Wu, Jixiang; Saha, Sukumar; Stelly, D. M.
Abstract : Chromosome substitution lines (CSLs) have been developed for selected chromosomes from two tetraploid species of Gossypium and are effective ways to target introgression of alleles from exotic tetraploid species into Upland cotton ( G. hirsutum L.) Genetic effects of chromosomes 1, 4, and 18 from Upland cotton (TM‐1), Pima cotton ( G. barbadense L.), and Hawaiian cotton ( G. tomentosum Nutt. ex Seem) were estimated by topcrossing TM‐1 and six isochromosomal CSLs with five upland cultivars and comparing F2 and F3 hybrids for agronomic and fiber traits. Data were analyzed according to an additive–dominance (AD) model. Additive genetic effects were greater than dominance effects for lint percentage, fiber uniformity, fiber strength, and elongation; whereas, dominance effects were greater than additive effects for boll weight, lint yield, fiber length, and fiber micronaire. All additive × environment effects were small. Dominance × environment effects were only significant for boll weight, lint yield, and fiber micronaire. Chromosome B04 and B18 from Pima cotton and T01 from Hawaiian cotton had significantly greater additive effects for lint percentage than homologs. Chromosomes 1, 4, and 18 from the three species generally showed negative additive effect on lint yield compared with cultivars. Chromosome 1 from Hawaiian cotton had greater additive effects on fiber length than homologs. Chromosomes 1 and 4 from Pima cotton showed greater additive effects on fiber strength than homologs. The magnitude of additive effects on important agronomic and fiber traits show that Pima cotton and Hawaiian cotton harbor useful alleles for Upland cotton breeding programs.